ANALISIS PENGARUH MODAL, TENAGA KERJA DAN LAMA MELAUT TERHADAP PENDAPATAN NELAYAN PAYANG DI KELURAHAN BLIMBING KECAMATAN PACIRAN KABUPATEN LAMONGAN - Putri Indah Lestari; Zainal Arifin; Yunan Syaifullah (Program Studi Ekonomi Pembangunan, 2020)
The purpose of this study was to determine how much the income of fishermen and the influence of capital, labor and sea time on the income of payang fishermen in Blimbing Village, Paciran District, Lamongan Regency. The data collection technique was by distributing questionnaires to 70 fishermen respondents, using simple random sampling method. The data processing technique used to test this research is to use the gross income formula TR=PXQ net income formula = TR-TC and analyze the data using multiple linear regression, hypothesis testing, and classical assumption. The results obtained by the average income received by payang fishermen is Rp. 250,282,857 in a month going to sea. While the results obtained from the results of the multiple linear regression equation are LogY=4.901+0.192Logx_1+0.910Logx_2+0.697Logx_3+e. The results showed that capital (X1), labor (X2) and sea time (X3) have a significant and positive effect on the income of payang fishermen in Blimbing Village, Paciran District, Lamongan Regency.